2005
DOI: 10.1182/blood-2005-03-1301
|View full text |Cite
|
Sign up to set email alerts
|

High-dose therapy intensification compared with continued standard chemotherapy in multiple myeloma patients responding to the initial chemotherapy: long-term results from a prospective randomized trial from the Spanish cooperative group PETHEMA

Abstract: IntroductionTreatment of patients with multiple myeloma (MM) is disappointing. In this regard, the Southwest Oncology Group (SWOG) experience on standard dose therapy in 7 consecutive, large phase 3 studies has shown median survival times of less than 3 years, irrespective of the treatment given. 1 In addition, the Programa para el Estudio de la Terapéutica en Hemopatía Maligna (PETHEMA) group found that increased doses of conventional chemotherapy did not result in significant prolongation of survival. 2 Fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
164
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(170 citation statements)
references
References 29 publications
1
164
0
2
Order By: Relevance
“…However, three randomized trials show that OS is similar whether ASCT is done early (immediately following four cycles of induction therapy) or delayed (at the time of relapse as salvage therapy) [89][90][91]. Further, in a Spanish randomized trial, patients responding to induction therapy failed to benefit from ASCT trial, suggesting that the greatest benefit from early ASCT may be mainly among the small proportion of patients with disease refractory to induction therapy [92]. Two randomized trials have found benefit with tandem (double) versus single ASCT, with the benefit primarily seen in patients failing to achive CR or VGPR with the first ASCT [93,94].…”
Section: Role Of Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%
“…However, three randomized trials show that OS is similar whether ASCT is done early (immediately following four cycles of induction therapy) or delayed (at the time of relapse as salvage therapy) [89][90][91]. Further, in a Spanish randomized trial, patients responding to induction therapy failed to benefit from ASCT trial, suggesting that the greatest benefit from early ASCT may be mainly among the small proportion of patients with disease refractory to induction therapy [92]. Two randomized trials have found benefit with tandem (double) versus single ASCT, with the benefit primarily seen in patients failing to achive CR or VGPR with the first ASCT [93,94].…”
Section: Role Of Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%
“…[5][6][7] However, not all trials have been able to demonstrate a survival advantage for auto-SCT in myeloma, and it is not clear if all or only a selected set of patients derive survival benefit from auto-SCT. [8][9][10] Nevertheless, auto-SCT performed early in the disease course, typically after four cycles of initial therapy, remains the most common approach in patients who are considered eligible to undergo the procedure. More recently, clinical trials incorporating novel therapies such as thalidomide and its analogs and the proteasome inhibitor bortezomib continue to redefine the role of auto-SCT in this new era.…”
Section: Introductionmentioning
confidence: 99%
“…28 Several prospective randomized trials confirmed a benefit with HDC when compared with conventional chemotherapy, [29][30][31][32] and this procedure has been part of the standard of care for over two decades. 33 In the 2000s, an improvement of clinical outcomes was observed with the advent of immunomodulatory drugs and proteasome inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…3,14 HDM at a dose of 200 mg/m 2 is considered to be the standard conditioning regimen. 14,17,18,30 However, a variety of strategies has been explored with the aim of improving the results of HDM 200 mg/m 2 , including dose escalation, 22 addition of other agents such as busulfan, thiotepa or TBI 14,15,[17][18][19][20][21][22] or, conversely, dose reduction as part of a tandem auto-SCT procedure, 20 with overall mixed results. Further evidence is however necessary on the best conditioning regimen.…”
Section: Discussionmentioning
confidence: 99%